How do you factor x2 - y2?

x2 − y2 = ( x − y ) ( x + y )

When multipled ( x − y ) by ( x + y ) then the terms in xy cancel out, leaving x2 − y2

( x − y ) ( x + y ) = x 2 + x y − y x − y 2

= x2 + xy − xy − y2 =

x2 − y2

Was this answer helpful?

  
   

3.5 (1)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question